Discourses of the vanishing : modernity, phantasm, Japan - Ivy, Marilyn (University of Chicago Press, 1995)
Japan today is haunted by the ghosts its spectacular modernity has generated. Deep anxieties about the potential loss of national identity and continuity disturb many in Japan, despite widespread insistence that it has remained culturally intact. In this provocative conjoining of ethnography, history, and cultural criticism, Marilyn Ivy discloses these anxieties--and the attempts to contain them--as she tracks what she calls the vanishing: marginalized events, sites, and cultural practices suspended at moments of impending disappearance. Ivy shows how a fascination with cultural margins accompani.